The Implementation Of Student Teams Achievvement Division (STAD) Technique To Improve Student’s Reading Comprehension - Indra Jayanti Damanik; Maria Handayani (Bilingual : Jurnal Pendidikan Bahasa Inggris, 2023)
This thesis is about the implementation of Students Teams Achievement Division (STAD) technique in reading comprehension. The aim of the research is to solve the students’ problems in reading comprehension by implement STAD technique. The researcher used Slavin theory of process STAD technique in the classroom such as teaching materials, assigning students to teams, determining base score and team building. In this thesis, the problem of the study justified as “Is Student Teams Achievement Division (STAD) technique appropriate to implement in Reading Comprehension at Grade Ten of SMK Negeri 1 Tebing Tinggi?” This thesis is descriptive quantitative study design, to describe the implementation of STAD technique in reading comprehension. The subject of this study was at grade ten students of SMA Negeri 1 Tebing Tinggi. X Adkl 2 which consist 39 students. The instrument of study ate test and questionnaire. To collect the data, the researcher implement STAD technique in the class through the process. Then giving the test to see the students’ achievement. The last was giving the questionnaire to see the students’ reponse towards the implementation of STAD technique. Based on the research finding, it states that the Student Teams Achievement Division (STAD) technique was implemented well in teaching learning process from teaching materials, assigning students to teams, determining base score and team building. Then the students’ result of test showed that the mean of students’ score was 76.79. This means that the result passed the minimum criterion of school is 76. The last, from the students’ response towards the STAD technique the STAD technique through questionnaire was 89.69% of students gave good response. From these findings, it states that student teams achievement division (stad) technique was appropriate to implement in reading comprehension at grade ten of SMK Negeri 1 Tebing Tinggi.